Endothelin type B receptor interacts with the 78‐kDa glucose‐regulated protein. Issue 6 (5th March 2019) - Mazaki, Yuichi; Higashi, Tsunehito; Onodera, Yasuhito; Nam, Jin‐Min; Hashimoto, Ari; Hashimoto, Shigeru; Horinouchi, Takahiro; Miwa, Soichi
Abstract : Endothelin (ET)‐1 is involved in the vascular system, cell proliferation and apoptosis. ET receptors consist of ET type A receptor (ETA R) and ET type B receptor (ETB R). ETA R and ETB R generally exhibit opposite responses, although many exceptions exist. In the present study, we attempted to identify ETA R‐ or ETB R‐specific binding proteins to understand the differences in ETA R‐ and ETB R‐mediated responses after ET‐1 stimulation. The 78‐kDa glucose‐regulated protein (GRP78) showed a stronger binding affinity towards ETB R than towards ETA R. Moreover, GRP78 overexpression promoted ETB R‐mediated ERK activation and GRP78 silencing suppressed ETB R‐mediated ERK activation. Furthermore, ETB R can localize GRP78 to the cell periphery. These results suggest that the interaction of ETB R with GRP78 affects ERK activation and GRP78 localization. Abstract :